1996
DOI: 10.1164/ajrccm.154.4.8887603
|View full text |Cite
|
Sign up to set email alerts
|

Six-month supervised intermittent tuberculosis therapy in Haitian patients with and without HIV infection.

Abstract: We enrolled 427 consecutive patients with tuberculosis diagnosed in Cité Soleil, Haiti in a trial of short-course intermittent therapy. All patients received supervised therapy with isoniazid, rifampin, pyrazinamide, and ethambutol thrice weekly for 8 wk, followed by isoniazid and rifampin thrice weekly for 18 wk. At entry, the 177 human immunodeficiency virus (HIV)-infected patients (42%) were found significantly more likely to have extrapulmonary tuberculosis and negative tuberculin skin tests (p < 0.05). Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 14 publications
4
73
1
6
Order By: Relevance
“…Of five prior publications in which recurrence data were compared and reported, none showed a statistically significant difference between HIV-infected and HIV-uninfected/unknown patients (8)(9)(10)(11)(12). The recurrence rate in HIV-infected individuals treated for tuberculosis was around 5% in all of these studies except one, which was located in an area of endemic tuberculosis and reported a high recurrence rate of 9% (11).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Of five prior publications in which recurrence data were compared and reported, none showed a statistically significant difference between HIV-infected and HIV-uninfected/unknown patients (8)(9)(10)(11)(12). The recurrence rate in HIV-infected individuals treated for tuberculosis was around 5% in all of these studies except one, which was located in an area of endemic tuberculosis and reported a high recurrence rate of 9% (11).…”
Section: Discussionmentioning
confidence: 96%
“…In general, treatment outcomes of conventional 6-month, rifamycin-based regimens for tuberculosis are reported as being equivalent in HIV-infected and HIV-uninfected individuals (7)(8)(9)(10)(11)(12). As a consequence, current guidelines recommend a 6-month, rifamycin-based course for all patients with drugsusceptible tuberculosis regardless of their HIV serostatus (2).…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…A study in Zaire among HIV-infected/AIDS-related TB patients demonstrated that additional 3 months in the continuation phase (2HRZE/7HR) of the standardized 6-month short-course regimen (2HRZE/4HR) resulted in 1% versus 8% of relapse rates, respectively but the survival rates were no different in patients given extended regimen (Perriens et al, 1995, as cited in Hopewell & Chaisson, 2000. Other studies revealed relapse rates of TB with various treatment regimens among HIV-infected/AIDS patients between 2%-7% (Kassim et al, 1995, as cited in Hopewell & Chaisson, 2000, Chaisson et al, 1996, as cited in Hopewell & Chaisson, 2000, el-Sadr et al, 1998, as cited in Hopewell & Chaisson, 2000. The United States CDC , the American Thoracic Society (ATS) and the Infectious Disease Society of America (IDSA) recommend the extension of the continuation phase from 6 to 9 months of the standardized 6-month rifampicin-based regimen for patients with positive cultures and cavitary TB, regardless of the HIV status (Chaisson & Nachega, 2010).…”
Section: Antituberculous Chemotherapymentioning
confidence: 95%
“…Some trials suggest that a 6-month short-course therapy is appropriate in HIV-1 [133][134][135], whilst others suggest prolonging the duration to 9 months. A retrospective review from the US showed no treatment failures in HIV-1 infected patients administered a 6 month standard rifampicin-based regimen but relapse rates were four-times higher in those treated for 6 months compared to those treated for longer [136].…”
Section: Management Of Tb In Hiv-1 Infected Persons Tb Therapy Duratimentioning
confidence: 99%